THE THERE WAS NO DIFFERENCE BETWEEN FINGER PAINTING AND MERONCE GAMES TO IMPROVED FINE MOTOR ON CHILDREN OF PRASEKOLAH AGE IN EDUCATION OF EARLY AGE CHILDREN IN DENPASAR CITY - Suryawan, I Nyoman Ari; Wibawa, Ari; Griadhi, I Putu Adiartha (Majalah Ilmiah Fisioterapi Indonesia; Vol 6 No 1 (2018): Majalah Ilmiah Fisioterapi IndonesiaDO - 10.24843/MIFI.2018.v06.i01.p08, 2018)
Finger Painting and meronce could enhance fine motor in children aged 4-6 years. Children in this period was good physical or psychological development. This study aimed to find out difference of finger painting and meronce to improved fine motor development of preschool children in early childhood in Denpasar. This study used Quasy Experimental Design with pre and post test with control Group Design. The samples were divided into three groups with 14 children each group. The sampling technique was random sampling. Statistical test used one-way ANOVA. The results obtained p = 0,000 (p <0.05) which showed no difference between playing finger painting and meronce to improve motor development of preschool children. This study showed between finger painting and meronce were effective to improve motor development of preschool children with p = 0.192 in LSD post hoc test. The conclusion of this study was Finger Painting Game can enhance the fine motor development of preschoolers. Meronce game could enhance fine motor development of preschoolers. Finger Painting and Meronce games were equally effective on improving fine motor of preschoolers. The results of this study could be useful to stimulate the fine motor development of preschool children. Key Words: Finger Painting, Meronce, fine motor